Communication ethics from the Qur'anic perspective: an analysis of selected contemporary exegeses - Solihin, Sohirin Mohammad; Osmani, Noor Mohammad (Hamdard Foundation Pakistan, 2018)
This research studies the ethics of dialogue and communication with others as embodied in the Qur’Én based on exegesis written by contemporary exegetes. It concentrates on verses which highlight the most appropriate manner to deal with others. The ethics of dialogue and communication comprises the whole aspect of sociological context which could be actualized in the form of the concept of knowledge for human benefits. In view of the lack of proficiency in Arabic, the most appropriate and convenient way of understanding the Qur’an is to look into the views of contemporary exegetes. Ethical guidelines in the Qur’an surveyed in this study may help the readers to be sensitized on handling relationship problems, religious and communal tension which have plagued our world today.